MANAJEMEN RESIKO PEMBIAYAAN MUDHARABAH PADA PERBANKAN SYARIAH (STUDI KASUS BANK MUAMALAT CABANG SURABAYA) - Joko Hadi Purnomo (LPPM Institut Agama Islam Al-Hikmah Tuban, 2017)
Banking is an institution that carries out three main functions, namelyreceiving money deposits, lending money, and money transfer services. In theeconomic history of the Muslims, bank functions have been known since the time of theProphet Muhammad. These functions are receiving assets, lending money forconsumption purposes and for business purposes, as well as sending money.Definition of banks according to the Banking Act No. 10 of 1998 is a business entitythat collects funds from the public in the form of deposits and distributes to the publicin the form of credit and / or other forms in order to improve the lives of many people.While the Islamic Bank is a bank that operates with sharia principles, which refers tothe Qur'an and the Hadith of the Prophet 2, meaning that the Islamic Bank isoperationally and theoretically following the Sharia provisions contained in theQur'an 'an and the Hadith of the Prophet, namely the procedures for Islamic worship.Risk management in mudharabah financing at Bank Muamalat Indonesia SurabayaBranch is an effort to minimize the risks that occur, both at the pre-contract and postcontractstages. Pre-contract mitigation is carried out by complying with theapplicable Standard Operational Procedures and other regulations established byinternal banks and external banks, rigorously selecting candidates for mudharib, andanalyzing the feasibility of prospective mudharib businesses. While post-contract riskmitigation by periodically monitoring the condition of mudarib business and fosteringmudharib business